Active substances of myxobacteria against plant diseases and their action mechanisms - Zhang, Lele; Bao, Liangliang; Li, Songyuan; Liu, Yang; Liu, Huirong (Frontiers in Microbiology, 2024)
Myxobacteria have a complex life cycle and unique social behavior, and obtain nutrients by preying on bacteria and fungi in soil. Chitinase, β-1,3 glucanase and β-1,6 glucanase produced by myxobacteria can degrade the glycosidic bond of cell wall of some plant pathogenic fungi, resulting in a perforated structure in the cell wall. In addition, isooctanol produced by myxobacteria can lead to the accumulation of intracellular reactive oxygen species in some pathogenic fungi and induce cell apoptosis. Myxobacteria can also perforate the cell wall of some plant pathogenic oomycetes by β-1,3 glucanase, reduce the content of intracellular soluble protein and protective enzyme activity, affect the permeability of oomycete cell membrane, and aggravate the oxidative damage of pathogen cells. Small molecule compounds such as diisobutyl phthalate and myxovirescin produced by myxobacteria can inhibit the formation of biofilm and lipoprotein of bacteria, and cystobactamids can inhibit the activity of DNA gyrase, thus changing the permeability of bacterial cell membrane. Myxobacteria, as a new natural compound resource bank, can control plant pathogenic fungi, oomycetes and bacteria by producing carbohydrate active enzymes and small molecular compounds, so it has great potential in plant disease control.